Vigor and Viability of Harvested Barley Seeds as Affectd by Phosphorus Levels and Nitrogen Fixing Bacteria - Kareem Ashfaq; Behzad Zafar; Shamsur Rehman; Iftikhar Shah; Subbuktageen Khan; Ubaid Ullah; Umar Farooq; Talha Hashim; Shahzeb Khan; Rizwan (International Journal of Advanced Technology and Social Sciences, 2023)
Out of three macro nutrients, phosphorus (P) is one of the main nutrients and necessary for plant growth. N2 fixing bacteria are microorganisms capable of transforming atmospheric nitrogen into fixed nitrogen. The presented research was conducted to estimate the effect of phosphorus levels and nitrogen fixing bacteria on the vigor and viability of harvested barley seeds at Agronomy Research Laboratory, The University of Agriculture Peshawar during Rabi season 2021-2022.   The experiment was laid out in randomized complete block design having four replications. The experiment is consisted of two-factors in which one factor was nitrogen fixing bacteria (with and without) and the other was phosphorus levels (40, 60 and 80 kg ha-1) with control. Analysis of variance revealed significant differences among all parameters and interaction. Based on experimental results phosphorus applied at the rate of 80 kg ha-1 significantly increased germination (86.25 %), germination rate (6.16), seedling length (21.82 cm) and root fresh weight (0.04 g). The application of nitrogen fixing bacteria shows positive response in all the parameters. N2 fixing bacteria significantly increased germination (86.50 %), germination rate (6.17), seedling length (20.60 cm) and root fresh weight (0.04 g). Interaction between phosphorus level and nitrogen fixing bacteria was found significant for seedling length and shoot fresh weight. It was concluded that phosphorus applied at the rate of 80 kg ha-1 with nitrogen fixing bacteria is recommended for increasing vigor and viability of harvested barley seeds